Manager plus efficacement mais sans perdre son âme dans l’économie sociale et solidaire - Samira Mahlaoui; Jean‐Paul Cadet; Michel Ronzy (Éducation et Socialisation)
How to manage the structures of the SSE and small cooperatives in particular, and thus face the tension between social values to prevail and profitability to obtain which characterizes this management, especially in a situation of crisis or change? A case study of administrative and commercial directors (DAC) of consumer cooperatives faced with a change of economic model, shows what it may mean in concrete terms to adopt the posture of cooperative entrepreneurship in such circumstances. The DACs involved in the co-analysis approach implemented now compare themselves to VSE managers and develop a managerial professionalism that aims to be more effective while seeking to remain attached to the cooperative framework and preserve their identity as cooperators.